Nursing care of a patient diagnosed with cholecystolithiasis, treated by laparoscopic surgery - Paulina Myszka; Weronika Nawłatyna; Piotr Pawłowski; Aneta Kościołek; Klaudia Jakubowska; Violetta Mianowana (Kazimierz Wielki University, 2019)
Introduction. Cholecystolithiasis is one of the most common abdominal disorders. Asymptomatic cholecystolithiasis treatment is not undertaken, when clinical symptoms of the disease occur, it is usually treated by laparoscopic or classical cholecystectomy. Currently, a laparoscopic method is recognized as the most beneficial and safest method for removing bile deposits. Aim. The aim of the study is to show the nursing problems of a patient diagnosed with cholecystolithiasis, treated by laparoscopic surgery. Methods and materials. The study was based on the individual case study method, using research techniques such as observation, nursing interview, documentation analysis and measurement. The research tools used for the study are the Individual Nursing Care Card, the Visual Analogue Scale - VAS and the Apfel Score to assess the risk of postoperative nausea and vomiting. Findings and conclusions: During the research process, 7 nursing diagnoses were made regarding health problems of the hospitalization period of a patient diagnosed with cholecystolithiasis, treated by a laparoscopic method. The patient after a surgery involving the removal of the gallbladder suffers from pain caused by tissue disruption, nausea, dizziness and anxiety manifested mainly in the evening, making it difficult for the patient to sleep soundly.